PENGARUH PEMBERIAN AROMA TERAPI LAVENDER TERHADAP INSOMNIA PADA LANSIA DI DESA KOTO TUO WILAYAH KERJA PUSKESMAS 2 XIII KOTO KAMPAR - ELVIDA JUNITA; GUSMAN VIRGO; ADE DITA PUTRI (Jurnal Ners, 2020)
Background Insomnia is a condition in which someone who experiences difficulty sleeping or sleep often wakes up at night or wakes up too early. There are several therapies that can be used are lavender aromatherapy. Inhaling lavender increases the frequency of alpha waves and this state is associated with relaxing (relaxation) so it can treat insomnia. Lavender also helps balance the body's health which is very useful in relieving headaches, premenstrual syndrome, stress, tension, muscle spasms and heart regulation. The purpose of this study was to determine the effect of lavender aroma therapy on reducing insomnia in the elderly in Koto Tuo Village, the working area of Puskesmas 2 XIII Koto Kampar. This research method is experimental, using a Quasy-experimental research design with 24 elderly people, data analysis using statistical t test. The results of this study showed that there was a decrease in insomnia. The statistical results of the t test showed that the value of p = 0.00, where there was an effect of lavender therapy on the quality of sleep in the elderly in Koto Tuo Village, the Work Area of Puskesmas 2 XII Koto Kampar. The conclusion that the average insomnia sufferer before giving lavender aromatherapy is 47.78 with a standard deviation of 7.55, and the average insomnia patient after giving lavender aroma therapy is 43.00 with a standard deviation of 8.714, and a p value of 0.00 (p.